Prezydencjalna odmiana systemu parlamentarnego w konstytucji kwietniowej: [Presidental variant of parliamentary system from the April Constitution] (Studia Prawnicze / The Legal Studies, 1984)
A characteristic feature of the interwar period was introducing parliamentary responsibility of the government and repudiating dualistic parliamentarism of the 19th century or replacing it by its modern version (Weimar Germany). The authors of the Constitution of 1935, while departing from parliamentarism of responsibility, tried to enliven the institution of the head of state in its modified form. In this formulation it is an element of new parliamentarism of balance. In the new constitution it is to counterbalance the predominance of the parliament characteristic of the French variant of parliamentarism. The president plays a very important role and the government becomes a link between it and the parliament. A leading role of the President could have been diminished by a party system but effective voting regulations of 1935 made it impossible.It also seems that elements comprised in the April Constitution going beyond the structure of parliamentarism of those days as well as foreign elements indicating presidentialism do not disturb a general outline of parliamentary form of government, thus it cannot be contradictory to it. Weakening the position! of the head of state and the supremacy of parliament is a later phenomenon characteristic of the form assumed by this system in the period of democratization of liberal state of the 19th century.While analyzing the model of parliamentary system comprised in the constitution, we have to remember that — apart from antiparliamentary resolutions of the Constitution — two opposing motives of the authors of the Constitution of 1935 influence it.Firstly, the form of parliamentary system was undoubtedly subordinated to the conception of presidency, which was a manifestation of eagerness for guaranting "sanacja" regime by law in Poland. Pilsudski's followers after the May coup d'etat faced a problem of strengthening the new order. In ;order to do lit the actual situation based on coercion had to be changed into binding state of law.Secondly, the authors of the April Constitution after all tried to create a modern system of parliamentarism of balance; where the president would play a role of a regulator of the system. Unfortunately, this system based on a strong position and, at the same time, Cooperation of the president with parliamentary majority never existed in practice. Voting regulations did not allow to create parliamentary majority supported by the majority of the society and without it the system could not function properly. Thus, after the possibility of cooperation of the president with parliamentary majority had been rejected, the evolution towards authoritarism began.Thus, while evaluating historical facts, and the April Constitution such a fact today, we can-not acknowledge that presidential version of parliamentary system included in it was completely pointless. The construction undoubtedly anticipated and paved the way for the solutions of the V French Republic.